Parental support and parental monitoring and relations to deviant behaviors among adolescent boys and girls in Iceland - Alexandra Marín Sveinsdóttir 1999-; Sara Ösp Eðvarðsdóttir 1991- (2024)
Adolescence is a period when young individuals start to establish themselves in the world and become more independent. Research has shown that deviant behavior in the form of violence and conduct disorder might appear throughout these years. Consequently, it is important to examine and identify possible preventive strategies that might be applied to avoid such behavior. The current study was a quantitative cross-sectional study that examined adolescents in 192 elementary schools in Iceland. The sample consisted of 2000 participants aged 14-16. Background information was gathered about the participants’ gender, grade, and year of birth. Independent variables were parental support and parental monitoring. Dependent variables were conduct disorder and violence. The result indicated that adolescents were less likely to engage in conduct disorder if their parents provided them with good support. Gender differences in deviant behavior were also observed, but boys were more susceptible than girls to exhibit deviant behavior. It can be concluded that the current study highlights the importance of strengthening the relationship between adolescents and parents with the aim of reducing deviant behavior that can be common during adolescence. Keywords: adolescents, parental monitoring, parental support, deviant behavior, violence, conduct disorder Unglingsárin er tími sem einkennist af því að unglingar fá aukið sjálfstæði og eru að fóta sig í lífinu. Rannsóknir hafa sýnt fram á að frávikshegðun í formi árásargirni og hegðunarröskun getur gert vart við sig á þessum árum og því mikilvægt að skoða og finna ákveðnar forvarnir sem geta nýst til að koma í veg fyrir slíka hegðun. Núverandi rannsókn var megindleg þversniðsrannsókn þar sem skoðaðir voru unglingar á aldrinum 14-16 ára í 192 grunnskólum á Íslandi, en í úrtakinu voru 2000 þátttakendur. Bakgrunnsupplýsingar voru fengnar með kyni, bekk og fæðingarári þátttakenda. Frumbreytur voru stuðningur foreldra og eftirlit foreldra. Fylgibreyturnar voru árásargirni og ...